Are we familiar with this rare indicative of a higher risk for breast cancer? - Altunkeser, Ayşegül; Arslan, Fatma Zeynep; Alkan, Ender; Günler, Tuğba (The European Research Journal, 2019)
Secretory adenosis (SA) of breast is rarely seen benign breast lesion, which might be associated with increased risk for breast carcinoma. SA is an extremely rare lesion, the cases reported in the literature and long-term follow-up studies are limited and radiological and histopathological diagnosis of SA is mostly challenging; it could be frequently misinterpreted as ductal carcinoma in situ. Because of these reasons; clinical significance and management of SA is still not fully understand and relative risk of SA is still not well-established. Herein; we presented mammography, ultrasound, magnetic resonance imaging and microscopic findings in a patient with SA of breast.